Kant’s Concept of Moral Autonomy as a Philosophical Justification of Party Autonomy - Prasetiyo, Eko Dwi (BANI Arbitration and Law Journal, 2025)
One of the important doctrines in international private law, especially in the field of contract law, is the party autonomy doctrine. Although it has gained enormous acceptance, there is still debate about the existence of the doctrine, as well as disagreements about the exact parameters, scope and boundaries of the doctrine. Kant's categorical imperative: "Act so that the maxim of thy will can always at the same time hold good as a principle of universal legislation," is the principle of individual moral autonomy as a universal law-making agent based on the autonomy of the will. This principle provides a philosophical justification for the existence of party autonomy. Based on Kant's idea, a categorical imperative is obtained that guides every rational being in viewing the doctrine of party autonomy, namely by giving respect to every free choice made by the parties in relation to disputes that occur between them. In this way, a transcendental understanding of party autonomy is obtained, which is respect for all rational beings to recognize and uphold every choice made by the parties in a dispute resolution that occurs.